Asymmetric Organocatalysis of Activated Alkynes and Enynes. Issue 7 (1st June 2021) - Sharma, Akashdeep; Nagaraju, Koppanathi; Rao, Gunda Ananda; Gurubrahamam, Ramani; Chen, Kwunmin
Abstract: Enantioselective organocatalytic protocols for the functionalization of electron‐deficient internal alkynes and enynes are reviewed. This review focuses on the applicability of activated conjugated π‐systems in asymmetric synthesis for providing diversified chiral entities under metal‐free reaction conditions. Various organocatalytic strategies with different catalytic modes are demonstrated. Abstract : Enantioselective organocatalytic syntheses were developed for the functionalization of electron‐deficient alkynes and enynes. These methods provide diversified chiral entities with different catalytic modes.